Information-seeking behaviour of students at the Medan Polytechnic of Health Sciences - Addary, Habibah Salsabila; Purwaningtyas, Franindya (Jurnal Informatio, 2026)
Background: The massive availability of health information presents a significant risk of medical misinformation. Although previous studies have examined general information-seeking behaviour, limited attention has been given to how health vocational students adapt established information-seeking models under academic and clinical pressures. Purpose: This study aims to map, explore, and reconstruct the information-seeking behaviour of health vocational students using David Ellis’s Information Seeking Behaviour Model, integrated with Risk Awareness and Evidence-Based Practice (EBP). Methods: This qualitative descriptive study employed a case study design involving seven final-year Diploma III students representing seven study programmes at Poltekkes Kemenkes Medan. Participants were selected through purposive sampling. Data were collected through semi-structured interviews supported by non-participant observation for methodological triangulation and analysed using an interactive model of data condensation, data display, and conclusion drawing. Results: Students demonstrated pragmatic information-seeking tendencies by prioritising efficiency during the starting, chaining, browsing, and extracting stages while consistently omitting the monitoring stage. However, during verification, they applied rigorous data triangulation by comparing clinical information with authoritative guidelines from the Ministry of Health and the World Health Organization. When information was considered invalid, students returned to the browsing stage, demonstrating a non-linear feedback pattern. Conclusion: The findings indicate that health vocational students reconstruct Ellis’s traditional model through a dynamic pattern termed Pragmatic Adaptation. This pattern reflects Risk Awareness Information Behaviour (RAIB), in which students balance search efficiency with rigorous verification to support evidence-based practice and reduce the risk of misinformation.